Semi-tethered load-velocity profiles - correlations with metabolic and dryland strength parameters in male and female squad swimmers - Wahl, P.; Keller, S. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION: Semi-tethered load-velocity profiling is a reliable method to estimate swimspecific neuromuscular capacities, i.e., theoretical maximal load (L0), speed (v0), and slope of the regression line (Slv), and can therefore be used for individual athlete characterization and training derivations (Olstad et al., 2020). For example, higher L0 and v0 values were observed in male compared to female front crawl swimmers (Olstad et al., 2020), higher L0 and lower v0 values were found in butterfly swimmers compared to front crawl swimmers (Gonjo et al., 2020). Despite high correlations between load-velocity profiles and 50 m performance (Gonjo et al., 2020), it is still unclear which metabolic or mechanical properties are associated with different semi-tethered load-velocity profiles. Therefore, we correlated anthropometric, dryland strength, and metabolic parameters with L0, v0, and Slv to elucidate underlying mechanisms between different profiles separately by sex.